Eating Our Own Cooking: Toward a Design Science of Research Methods - Venable, John; Baskerville, Richard (Academic Publishing Limited, 2012)
This paper argues that Design Science is an appropriate paradigm for research into Research Methods. Research Methods are designed and created by people to achieve a specific purpose –creating new knowledge. Research methods vary in utility depending on how well they their purpose in the particular contexts and contingencies for which they were developed. Applying a DSR perspective to research methods should yield increased utility in the application of research methods, better guidance in applying them and greater confidence in achieving the desired outcomes of applying them. Based on these premises, this paper analyses the logical consequences of taking a Design Science perspective on research methods. First, it analyses the various purposes of research methods to clarify the alternative and competing design goals of research methods. Second, it analyses and characterises the types of design artefacts that comprise research methods. Third, it considers issues of the evaluation of research methods. Fourth and finally, it considered the development of design theories of research methods.